Case Report: Syphilitic Hepatitis–A Rare and Underrecognized Etiology of Liver Disease With Potential for Misdiagnosis - Al Dallal, Hiba A.; Narayanan, Siddharth; Alley, Hanah F.; Eiswerth, Michael J.; Arnold, Forest W.; Martin, Brock A.; Shandiz, Alaleh E. (Frontiers in Medicine, 2021)
Syphilitic hepatitis (SH) in adults is a rare condition that can be easily misdiagnosed. Clinical and histopathologic manifestations of SH can mimic other infectious and non-infectious conditions, and the diagnosis should be considered in all at-risk patients with abnormal liver function tests. We present an unusual case of SH presenting with seizures and multiple liver lesions. This case report, in line with other newly published reports, promotes awareness of SH as a rare manifestation of treponemal infection and highlights the importance of including SH in the differential diagnosis for patients at risk for sexually transmitted infections and presenting with liver enzyme abnormalities. From a hospital quality control and socioeconomic perspective, our case adds to the growing body of evidence that demonstrates an increasing incidence of patients suffering from venereal diseases and injection drug use disorders and the burden these conditions place on the healthcare system. Recognition of the clinicopathologic features of SH is required to prevent missed diagnosis and to foster systematic crosstalk between healthcare staff and public health personnel managing this problem.